2003
DOI: 10.1007/s00440-003-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for densities of uniformly elliptic random variables on Wiener space

Abstract: In this article, we generalize the lower bound estimates for uniformly elliptic diffusion processes obtained by Kusuoka and Stroock. We define the concept of uniform elliptic random variable on Wiener space and show that with this definition one can prove a lower bound estimate of Gaussian type for its density. We apply our results to the case of the stochastic heat equation under the hypothesis of unifom ellipticity of the diffusion coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
88
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(90 citation statements)
references
References 18 publications
1
88
1
Order By: Relevance
“…5, we establish a lower bound on p t,x , which proves Theorem 1.1(b). This upper (respectively lower) bound is a fairly direct extension to d ≥ 1 of a result of Bally and Pardoux [2] (respectively [7]) when d = 1. In Sect.…”
Section: Introduction and Main Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…5, we establish a lower bound on p t,x , which proves Theorem 1.1(b). This upper (respectively lower) bound is a fairly direct extension to d ≥ 1 of a result of Bally and Pardoux [2] (respectively [7]) when d = 1. In Sect.…”
Section: Introduction and Main Resultsmentioning
confidence: 72%
“…, u(t, x k )) is absolutely continuous with respect to Lebesgue measure, with a smooth and strictly positive density on {σ = 0} k , provided σ and b are infinitely differentiable functions which are bounded together with their derivatives of all orders. A Gaussian-type lower bound for this density is established by Kohatsu-Higa [7] under a uniform ellipticity condition. Morien [8] showed that the density function is also Hölder-continuous as a function of (t, x).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was generalized by Kohatsu-Higa [9] in Wiener space via the concept of uniformly elliptic random variables; these random variables proved to be well-adapted to studying diusion equations. E. Nualart [13] showed that fractional exponential moments for a divergence-integral quantity known to be useful for bounding densities from above (see formula (1.1) below), can also be useful for deriving a scale of exponential lower bounds on densities; the scale includes Gaussian lower bounds.…”
mentioning
confidence: 99%